Antioxidant activities of threadfin bream (nemipterus japonicus) hydrolysate and its effect on oxidative stability of frying oil / Normah Ismail, Mohd Faizzuddin Mustapa Kamal and Kyaw Zay Ya - Ismail, Normah; Mustapa Kamal, Mohd Faizzuddin; Zay Ya, Kyaw (Universiti Teknologi MARA Shah Alam, 2020)
The antioxidant activities and oxidative stability of palm olein frying oil added with threadfin bream (TFB) hydrolysate and Nanox 189 were studied. The DPPH radical scavenging activities and chelating effects of ferrous ion were evaluated and compared with α-tocopherol. Oxidative stability after 30 frying cycles were analysed for the induction period, free fatty acids (FFA), peroxide values (PV), total polar compounds (TPC), and viscosity. Palm olein without any antioxidant was used as control. Nanox 189 exhibited a higher percentage on the DPPH scavenging effect and ferrous ion chelating effect than TFB hydrolysate. Frying oil added with Nanox 189 recorded the longest induction period, which was up to 11 hr. while TFB hydrolysate added oil showed an induction period of nine hours. Nanox 189 addition in frying oil yielded the lowest FFA and PV, followed by those added with TFB hydrolysate. The highest readings of TPC were recorded for TFB hydrolysate added oil, which is 13%. Throughout the 30 frying cycles, the addition of TFB hydrolysate recorded a lower percentage increase for viscosity than Nanox 189 with 4.7% compared to the latter, which is 9.6%. Even though the antioxidant activities of TFB hydrolysate was lower than that of Nanox 189, the study suggested some antioxidant potential of TFB hydrolysate based on the DPPH radical scavenging activities and chelating effects of the ferrous ion as well as its ability to slightly improve the oxidative stability of palm olein during the 30 frying cycles.